Coercive Measures in Criminal Proceedings - Róth, Erika (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
This chapter introduces the basic problems of coercive measures applicable in criminal proceedings. The fundamental rights of the suspect or accused can be restricted in several forms to ensure the effective completion of an investigation and, if necessary, the court procedure. Coercive measures restricting personal liberty are the most serious limitations and should be of interest to international organizations protecting fundamental/human rights and empirical studies. Although we examine the relevant provisions of the national codes of criminal procedures of the Central European countries,1 we will use this background material to refer to them only as examples. Considering the scope and complexity of the provisions, it would not be possible to outline the main rules concerning coercive measures in different states.KEYWORDS: coercive measures, criminal procedure, custody, fundamental rights, pre-trial detention